Superior Outcomes Using Normothermic Regional Perfusion in CDCD Liver Transplantation. (July 2018) - Hessheimer, Amelia; Coll, Elisabeth; Valdivieso, Andrés; Gómez, Manuel; Santoyo, Julio; Ramírez, Pablo; Gómez-Bravo, Miguel Ángel; López-Andujar, Rafael; Villar, Jesús; Jiménez, Carlos; Lluís, Félix; Lladó, Laura; et al.
Abstract : While there is increasing interest in its use, definitive evidence demonstrating superiority of normothermic regional perfusion in controlled donation after circulatory death liver transplantation has not been presented. Unlike the rest of the Western world, where use of NRP has been anecdotal, 25% of all cDCD donors that have been performed in Spain since 2012 have included post-mortem NRP. Aim: Analyze the first years of the Spanish experience with cDCD liver transplantation, in particular regarding the impact post-mortem NRP has had on organ utilization rates and transplant outcomes. Methods: Data was collected regarding potential cDCD liver donors and transplants that resulted between 2012 and 2016. All transplants had at least 6 mos of follow-up. Each donor hospital determined the process by which organs were recovered: NRP with pre-mortem cannulation, NRP with post-mortem cannulation, or super rapid recovery. Results: From 2012 to 2016, 370 potential cDCD liver donors were evaluated: 152 with NRP and 218 with SRR. Ultimately, rates of liver transplantation were 64% NRP and 57% SRR (P=0.102). Among livers that were transplanted, median donor age was 57 (46-65 IQR). While there were no differences in terms of relevant donor or recipient characteristics when analyzed according to recovery method, the functional warm ischemia time was shorter when NRP was applied – 12 (10-16) NRP vs. 15 (11-20) SRR – given that in most cases femoral cannulae were placed prior to withdrawal of care. While rates of early allograft dysfunction (22% NRP vs. 29% SRR) and PNF (2% NRP vs. 4% SRR) did not vary, rates of overall biliary complications (9% NRP vs. 24% SRR, P=0.006) and ITBL (2% NRP vs. 12% SRR, P=0.01) were significantly improved among recipients of livers recovered with NRP. One-year graft survival was 87% NRP vs. 78% SRR (P=0.110). On multivariate analysis analyzing risk factors for ITBL (including fWIT), the only significant factor was the organ recovery method used. Conclusions: This is the first large series describing the application of NRP in cDCD liver transplantation. While results with SRR were acceptable, results using NRP were superior and comparable to those achieved using standard-quality livers, even in spite of advanced donor age.